A historical perspective of liposomes-a bio nanomaterial. (2021) - Sharma, Vikash Kumar; Agrawal, Manoj Kumar
Abstract: Liposomes, a bio nanomaterial are known as drug delivery agents as they have their unique properties. A liposome encapsulates contained by a hydrophobic membrane a region of aqueous solution; this liquefies hydrophilic solutes which is not able to go through the lipids. Hydrophobic chemicals are also dissolvable in the membrane. Likewise Liposome carries both hydrophilic molecules and hydrophobic molecules. In order to bring the 10 sites action of molecules, the lipid bilayer may be combined along with different bilayers as the cell membrane carries the elements of liposome. Liposomes are used as artificial cell models. The objective of this paper is to present a picture of how liposomes (a bio nanomaterial) came into being as drug delivery agents, its advantages and disadvantages and discuss its present status, the recent developments and the future prospectus.